Effect of Price, Location, and Store Atmosphere on Purchasing Decisions at Islamic Boarding School Cooperatives Mamba'us Sholihin Suci Manyar Gresik. (Studies on the Gresik Sacred Society) - Reza Askrun Ashadi; Sukaris Sukaris (Universitas Muhammadiyah Gresik, 2022)
Retail development in Indonesia has experienced rapid development from year to year. This requires business people to maintain business with innovation and creativity. Retail development in the City Gresik, of course, also continues to experience development, especially in Mamba'us Sholihin Islamic Boarding School, Suci Gresik. Kepontren makes prices, locationsand store atmosphere to drive customer purchasing decisions, The purpose of this study was to determine the effect of price, locationand store atmosphere partially to purchasing decisions. Price,location and store atmosphere are independent variables in the study this, while the purchase decision is the dependent variable inthis research. This research is a quantitative research, with determination sample using purposive sampling and data collection techniques done by means of a questionnaire (questionnaire). The sample used in this study a number of 96 people. Then analyzed the data with using the Research Instrument Test, Classical Assumptions Test, Analysis Techniques Data and Hypothesis Testing. The results of this study are location and store atmospherehas a positive and significant influence on purchasing decisions,while the price has a positive and not significant effect on buying decision.